AES Parallel Implementation on a Homogeneous Multi-Core Microcontroller - Al-Bahri, Mohammed Said; Gupta, Kunal; AlShebani, Aqdar Jaber; AlAwaisi, Omnia Khamis (2018 International Conference on Current Trends Towards Converging Technologies (ICCTCT), 2018)
The new technology paradigm of the Industrial Internet revolution, namely, the Internet of Things have been considered one of the most important technology for the near future, that has seen vast and rapid leaps in the past few years. The global network, which connects machines and devices, interacting to provide us with an enhanced sense of connectivity has overwhelmed the industries and researchers have been working endlessly to enhance the working of these networks. In our paper we analyze the security aspects of the communication between the nodes that makes it all possible. We evaluate the working of the Encryption algorithms that controls the authentication procedure in the sensor network using the microcontrollers. The Advanced Encryption Standard has been rightly suggested as the most suitable symmetric cipher for wireless sensing network applications. However, when AES is implemented it would rather be slow and can consume relatively significant amount of time to run to completion. Our aim in this research is to increase the speed processing of AES encryption algorithm using the parallel and sequential mechanism and comparing the performance result between them. This work revolves around working with the key sizes of 192 which has around 90% enhancement and in 256 key size an enhancement of 89% has been established. Our implementation is believed to be the first proposed work for deploying AES in a homogenous multicore microcontroller.